2007
DOI: 10.1016/j.jocn.2005.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the histological and immunohistochemical features of the thymus in young- and elderly-onset myasthenia gravis without thymoma

Abstract: We performed histological and immunohistochemical analyses of the removed thymus in 20 elderly (onset age >60 years) and 23 young (onset age <40 years) patients with myasthenia gravis (MG) who showed positive anti-acetylcholine receptor (AChR) antibodies in serum without associated thymoma. In the elderly group nine (45%) demonstrated accumulations of lymphocytes indicating atrophied thymus without the basic structure. The elderly MG patients with atrophied thymic tissues showed higher titers of the anti-AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Так, W. Ishii и соавт. в 2005 г. при сравнении ткани тимуса пациентов с ранним и поздним началом миастении без тимомы не обнару-жили каких-либо значимых отличий [23]. К таким же выводам пришел J.…”
Section: лекции и обзорыunclassified
See 1 more Smart Citation
“…Так, W. Ishii и соавт. в 2005 г. при сравнении ткани тимуса пациентов с ранним и поздним началом миастении без тимомы не обнару-жили каких-либо значимых отличий [23]. К таким же выводам пришел J.…”
Section: лекции и обзорыunclassified
“…До сих пор нет общепринятого понимания, какой возраст манифестации миастении считать позд-ним. Ряд авторов определяют эту границу в возрасте 40-50 лет [8,[22][23][24][25], а другие -в возрасте 60 лет и старше [26,27].…”
Section: лекции и обзорыunclassified
“…Nikolic et al [28] investigated 138 thymectomized patients with GMG and found that complete stable or pharmacological remission were frequently observed in patients with a normal thymus (63.6%) and thymic lymphoid follicular hyperplasia (39.7%) and rarely observed in patients with thymoma (29.0%) and thymus atrophy (7.7%). In contrast, other studies have reported that thymus histopathology did not predict postoperative MG remission [22,26,27,29,30] . Chen et al [29] observed that B-cell activating factor receptor, CD19, and CD21 were not only increased in the hyperplasic thymus but also in the atrophic thymus, and patients with a hyperplasic thymus or atrophic thymus exhibited parallel postoperative prognoses.…”
Section: Discussionmentioning
confidence: 65%
“…Chen et al [29] observed that B-cell activating factor receptor, CD19, and CD21 were not only increased in the hyperplasic thymus but also in the atrophic thymus, and patients with a hyperplasic thymus or atrophic thymus exhibited parallel postoperative prognoses. Ishii et al [30] speculated that lymphocyte accumulation in the atrophic thymus indicates that residual thymus may also contribute to the immunopathogenesis of MG as a potential location for the induction of anti-AChR antibodies, despite hyperplasic thymus being considered the main source of AChR antibodies in AChR-MG pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…The borderline between the early and late onset of MG is usually around 50 years old for the following reasons: (1) the sex ratio in MG patients reverses at this age; and (2) this age is just between the two peaks of early onset and late onset [29,30]. However, some researchers have described that the boundary should be at 40 years old based on the thymus pathology, while others have set it at 60 years old based on HLA and the autoantibody profile [31,32]. Patients with an onset at older than 65 years old are usually called elderly-onset MG.…”
Section: Non-thymomatous Mg (Anti-achr Antibody-positive)mentioning
confidence: 99%